A structure-based concept of genocidal intent - Vest, Hans (Journal of international criminal justice, 2010)
The concept of genocidal intent developed in this article starts with an analysis of the structural particularities of the crime of genocide whose specific intent refers not only to the consequence(s) of personal conduct, but also to those of collective undertaking. The proposal submitted suggests understanding intent to destroy a protected group as such as a particular kind of specific intent: formally as intention to achieve a consequence which goes beyond the result that constitutes the actus reus. Materially, the proposed degree of intent refers to a two-fold approach which is based on a volitional ( intent ) and/or a cognitive ( certain knowledge ) element. Every element may be decisive depending on the mental state of the accused: either by virtue of the underlying purpose or by virtue of a certainty standard. While the consequences of the perpetrator's own conduct must be virtually certain, the adequate threshold for the occurrence of the (intended) overall action's result is practical certainty. In practice, such level(s) may be proven by exactly the same kind of circumstantial evidence current case law has relied on